Diagnosis of Ia–Ic stages of serous high-grade ovarian cancerby the lipid profile of blood serum - Mariia V. Iurova (IP Berlin A.V., 2021)
Background. Ovarian cancer is the first fatal malignancy of the female reproductive system. Early detection is associated with better outcomes, but is significantly difficult because of asymptomatic or low-symptomatic course.